Saneamento básico: uma percepção de qualidade de vida dos moradores do bairro São João e centro no município de Araguaína-TO. - Silva, Kacio Gomes da (Universidade Federal do Tocantins, 2023)
This study presents a survey on basic sanitation: a perception of the quality of life of residents of São João and Centro neighborhoods in the municipality of Araguaína -TO. In this way, the general objective of this study was to identify the perception of the residents about improvements in quality of life with basic sanitation. The question is: What are the improvements in quality of life with basic sanitation? For that, a comparative analysis of the São João and Centro neighborhood and other neighborhoods in the municipality of Araguaína -TO was carried out. The research is characterized as exploratory and qualitative, and data were generated semi-structured interviews with 15 residents of the São João neighborhood, 15 residents of the Center and 15 residents of other neighborhoods, totaling 45 respondents between May and June of 2019. It is considered that residents have a good perception about the importance of basic sanitation, since it can contribute with improvements, like quality of life for all and also in the development of the city.